ADULTS – CHILDREN POWER RELATIONS IN JUDY BLUME'S BLUBBER - Kurnia, Nandy Intan; Purbani, Widyastuti; Sugiarto, Tri (Diksi, 2021)
(Tittle: Adults-Children Power Relations in Judy Blume's "Blubber"). This study aims to uncover the power relations between adults and children in Judy Blume's novel entitled Blubber. This study used a qualitative method by paying attention to the expressions used in the novel related to the topic of power relations of adults-children. Peer debriefing techniques were applied in this study in order to achieve the validity of the research results. The collected data of dialogues and narrations suggest that adults assert dominance toward children especially physically and psychologically as a consequence of the adults' ideologies while trying to retain the image of a mentor. On the other hand, they also give spaces for children to grow and develop themselves. The research also revealed how Blubber paints a more realistic depiction of children and explores more of their human nature beyond images of innocence and naivety.             Keywords: abuse, Blubber, children's literature, egalitarian, power relations